Battery, positive pole piece, slurry, dispersing agent and preparation method

By using polyester compound dispersants in lithium-ion battery cathode slurries, the problem of insufficient dispersibility was solved, the uniformity and flexibility of the electrode were improved, and the capacity and stability of the battery were enhanced.

CN121366947APending Publication Date: 2026-01-20CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410961343.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-17
Publication Date
2026-01-20

AI Technical Summary

Technical Problem

Insufficient dispersion of the positive electrode slurry in lithium-ion batteries leads to poor uniformity and flexibility of the positive electrode sheet, affecting the battery's capacity retention and stability.

Method used

A dispersant containing polyester compounds is used, in which ester groups and solvated segments are introduced. The dispersibility is improved through polarization and steric hindrance, thereby improving the uniformity and flexibility of the electrode.

Benefits of technology

It improves the dispersibility of the positive electrode slurry and enhances the uniformity and flexibility of the positive electrode sheet, thereby improving the battery's capacity retention and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121366947A_ABST
    Figure CN121366947A_ABST
Patent Text Reader

Abstract

The invention discloses a battery, a positive pole piece, slurry, a dispersing agent, a preparation method and electric equipment. The battery comprises a positive electrode plate, the positive electrode plate comprises a current collector and a positive electrode material layer arranged on at least one side of the current collector, the positive electrode material layer comprises a positive electrode active material and a dispersant, the dispersant comprises a polyester compound, the polyester compound comprises a structural unit A and / or a structural unit B, the chemical formula of the structural unit A is shown in the specification, and the chemical formula of the structural unit B is shown in the specification. R1 and R2 are respectively selected from at least one of C0, a C1-C18 alkyl group and a C6-C18 aryl group; and R3 and R4 are respectively selected from at least one of H, C1-C18 alkyl groups, C6-C18 aryl groups and ester groups. The dispersing agent can improve the dispersibility of the positive electrode slurry and improve the uniformity and flexibility of the positive electrode plate, so that the battery has relatively high capacity and stability.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of new energy, in particular to a battery, a positive electrode sheet, a slurry, a dispersant, a preparation method and an electric device. BACKGROUND

[0002] Lithium ion batteries have high energy density and are widely used in wireless communication, transportation, aerospace and other aspects. In the preparation process of the lithium ion battery, the positive electrode sheet is usually prepared by coating the positive electrode slurry on the current collector and drying. Therefore, the properties of the positive electrode slurry affect the electrochemical performance and stability of the positive electrode sheet, and further affect the performance of the battery.

[0003] Among them, the insufficient dispersion of the positive electrode slurry will reduce the uniformity of the positive electrode sheet, resulting in loss of battery capacity; when the coating thickness and the compaction density of the positive electrode slurry are large, the positive electrode sheet will be brittle, the stability will be reduced, and the positive electrode sheet will be easily broken. The above statements are only used to provide background technical information related to the present application, and do not necessarily constitute the prior art. SUMMARY

[0004] The technical problem solved by the present application is to provide a battery, a positive electrode sheet, a slurry, a dispersant, a preparation method and an electric device, which can improve the dispersion of the positive electrode slurry, improve the uniformity and flexibility of the positive electrode sheet, and make the battery have high capacity retention rate and stability.

[0005] To solve the above technical problems, one technical solution adopted by the present application is to provide a battery, the battery comprising a positive electrode sheet, the positive electrode sheet comprising a current collector and a positive electrode material layer arranged on at least one side of the current collector, the positive electrode material layer comprising a positive electrode active material and a dispersant, the dispersant comprising a polyester compound, the polyester compound comprising a structural unit A and / or a structural unit B, the chemical formula of the structural unit A being The chemical formula of the structural unit B is Among them, R1, R2 are respectively selected from at least one of C0, C1-C18 alkyl, C6-C18 aryl; R3, R4 are respectively selected from at least one of H, C1-C18 alkyl, C6-C18 aryl, ester group.

[0006] In this embodiment, the dispersant provided selects a polymer with polyester as the main body in the main chain. The ester group in the polyester is a strong polar group, which can produce strong polarization effect. Further, the solvent chain segment can be introduced on the polyester side chain to make it fully stretch in the solvent system, which can improve the dispersion of the positive electrode slurry and improve the uniformity of the positive electrode sheet. In addition, the carbon chain in the ester group can rotate freely, which improves the flexibility of the electrode sheet, so that the battery has high capacity retention rate and stability.

[0007] In an embodiment, the chemical formula of the ester group is wherein 0≤a≤6, R' is selected from any one of C1-C18 alkyl, C6-C18 aryl, polyoxyethylene ether segment, polyoxyethylene polyoxypropylene ether copolymer segment. In this embodiment, the introduction of carbon chain or polyether segment can be fully stretched as a solvating segment in the solvent system, play a steric hindrance effect to improve the dispersion capacity and subsequent stabilization effect, prevent the particles from re-aggregating after complete dispersion.

[0008] In an embodiment, the polyoxyethylene polyoxypropylene ether copolymer segment comprises wherein 3≤b≤60; 0≤c≤60. The polyoxyethylene polyoxypropylene ether copolymer segment can be a solvating segment, and the degree of polymerization is within the above range, which has a good solvating effect and improves the dispersion performance.

[0009] In an embodiment, the positive active material comprises one or more of lithium iron phosphate and lithium manganese iron phosphate, which can improve the stability of battery performance.

[0010] In an embodiment, the coating amount of the positive material layer is 300-450 g / 1540.25 mm 2 . In this embodiment, the flexibility of the pole piece is improved.

[0011] In an embodiment, the compaction density of the positive material layer is 2.4-2.8 g / cm 2 . In this embodiment, the flexibility of the pole piece is improved.

[0012] In an embodiment, the sheet resistance of the positive pole piece is 0.05Ω-0.30Ω. The sheet resistance of the positive pole piece is small, which is conducive to reducing the internal resistance of the battery.

[0013] In an embodiment, the polyester compound comprises structural unit C and / or structural unit D, the chemical formula of structural unit C is the chemical formula of structural unit D is wherein R5 is selected from any one of C1-C18 alkyl and C6-C18 aryl. In this embodiment, the provided polyester compound can be obtained by polycondensation of a polybasic acid and a dibasic alcohol, or by polycondensation of a polyhydric alcohol and a dibasic acid. The carbon chain between the two ester groups in the polyester compound molecule can rotate freely, providing a certain flexibility; by regulating the carbon chain, the flexibility effect can be regulated.

[0014] In an embodiment, the polyester compound further comprises at least one substituent group G, G comprises any one of a carboxylic acid group and its derivatives, a sulfonic acid group and its derivatives, a phosphonic acid group and its derivatives. The substituent group G can ionize a negative ion, and then produce adsorption on the surface of the active material through the positive and negative charge effect, so as to produce electrostatic repulsion between the material particles, so as to achieve the dispersion purpose; or the substituent group G is a polar group, which can produce a strong interaction force with the material surface, so as to keep a certain distance between the material particles, thereby further improving the dispersion effect of the dispersant.

[0015] In an embodiment, G is an end group of the polyester compound. Through this arrangement, the dispersant can better interact with the active material, thereby improving the dispersion effect.

[0016] In an embodiment, the chemical formula of the carboxylic acid group and its derivatives is and / or the chemical formula of the sulfonic acid group and its derivatives is wherein, the value range of d is greater than 1 and less than or equal to 12, R6 is selected from any one of H, alkyl, alkyl alcohol, alkyl hydroxylamine, fatty ester group, aromatic ester group; the chemical formula of alkyl is the chemical formula of alkyl alcohol is the chemical formula of alkyl hydroxylamine is the chemical formula of fatty ester group is the chemical formula of aromatic ester group is The value of e is 1-12, the value of f is 1-16, and the number of carbon atoms in Ar is not more than 12.

[0017] In this embodiment, C d is a carbon atom chain, which can play a solvation effect as a solvation segment; when R6 is H, the above group can ionize a negative ion, and then produce adsorption on the surface of the active material through the positive and negative charge effect, so as to produce electrostatic repulsion between the material particles, so as to achieve the dispersion purpose; when R6 is alkyl, alkyl alcohol, alkyl hydroxylamine, fatty ester group and aromatic ester group, the polarity of the substituent group G can be improved, and a strong interaction force can be produced with the material surface, so as to keep a certain distance between the material particles, thereby further improving the dispersion effect of the dispersant.

[0018] In an embodiment, the chemical formula of the phosphonic acid group and its derivatives is wherein, R6 is selected from any one of H, alkyl, alkyl alcohol, alkyl hydroxylamine, fatty ester group, aromatic ester group; the chemical formula of alkyl is the chemical formula of alkyl alcohol is the chemical formula of alkyl hydroxylamine is the chemical formula of fatty ester group is the chemical formula of aromatic ester group is e is 1-12, f is 1-16, and the number of carbon atoms in Ar is no more than 12.

[0019] When R6 is H, the above group can ionize a negative ion, and then produce adsorption on the surface of the active material through the action of positive and negative charges, so as to produce electrostatic repulsion between the material particles, achieving the purpose of dispersion; when R6 is alkyl, alkyl alcohol, alkyl hydroxylamine, fatty ester group and aromatic ester group, the polarity of the substituted group G can be improved, and a strong interaction force with the material surface can be produced, so that the material particles maintain a certain distance, thereby further improving the dispersion effect of the dispersant.

[0020] In an embodiment, the dispersant comprises a structure as shown in formula (1) or a structure as shown in formula (2);

[0021]

[0022] wherein n is 3-100, A is an end-capping group, the end-capping group comprises an alkoxy phenyl alkoxy ester group ester group amide group one or more of hydroxyl -OH, amino -NH2 and carboxyl -COOH, g is 1-12, C h is an alkyl segment or an aryl-containing segment, h is 1-18, and R is H, C1-C12 alkyl or C6-C12 aryl.

[0023] In this embodiment, the provided dispersant selects a polymer with polyester as the main body in the main chain. The ester group in the polyester is a strong polar group, which can produce strong polarization. Multiple ester groups with similar distances can combine together to produce strong intermolecular forces on the surface of the material particles and then be adsorbed, so that the particle surface forms a double-layer structure to produce electrostatic repulsion. At the same time, the oxygen atom on the ester group can also produce hydrogen bond action with the group with weak polarity on the particle surface. Further, a solvated segment can be introduced on the polyester branched chain to make it fully stretch in the solvent system, play a steric hindrance role to improve the dispersion capacity and subsequent stabilization effect, and prevent the particles from re-aggregating after complete dispersion. Furthermore, the carbon chain between the two ester groups in the polyester compound molecule can rotate freely, providing a certain flexibility. When applied to the electrode sheet, the polyester compound can be embedded into the rigid binder (such as PVDF) chain to increase the sliding ability of the PVDF chain and improve the flexibility of the electrode sheet.

[0024] In an embodiment, the weight percentage of the substituent group G segment in the polyester compound is less than 15%, the weight percentage of the solvating segments R1, R2, R3, R4, R5 is less than 65%, and the weight percentage of the polyester group is 3%-30%. By controlling the weight percentage of each group in the polyester compound within the above range, good adsorption between the dispersant and the material particles and between the dispersant and the dispersion medium can be achieved, so as to achieve good dispersion effect, and at the same time, the polymer molecular chain has good flexibility.

[0025] In an embodiment, the weight average molecular weight of the polyester compound is 500-100000. The dispersant has a large molecular weight, which can generate strong steric hindrance effect, so as to fully disperse the material particles, and at the same time, the re-agglomeration of the particles can be reduced.

[0026] In an embodiment, the weight average molecular weight of the polyester compound is 2000-50000. The weight average molecular weight of the dispersant is within the above range, which can further disperse the material particles through physical isolation effect, and at the same time, the re-agglomeration of the particles after dispersion can be reduced.

[0027] To solve the above technical problems, another technical solution adopted by the present application is to provide a positive electrode slurry, comprising a positive electrode active material, a dispersant and a solvent, wherein the dispersant comprises a polyester compound, and the polyester compound comprises a structural unit A and / or a structural unit B. The chemical formula of the structural unit B is wherein R1 and R2 are at least one selected from C0, C1-C18 alkyl and C6-C18 aryl; and R3 and R4 are at least one selected from H, C1-C18 alkyl, C6-C18 aryl and ester group.

[0028] In this embodiment, the positive electrode slurry has good dispersibility, which is beneficial to improve the uniformity and flexibility of the positive electrode sheet.

[0029] In an embodiment, the dispersant accounts for 0.01%-3.0% of the total weight of the positive electrode slurry. When the dispersant accounts for the total weight of the positive electrode slurry within the above range, the flexibility of the positive electrode sheet and the energy density of the battery can be considered.

[0030] In an embodiment, the dispersant accounts for 0.03%-2.0% of the total weight of the positive electrode slurry. When the dispersant accounts for the total weight of the positive electrode slurry within the above range, the flexibility of the positive electrode sheet and the energy density of the battery can be further considered.

[0031] In an embodiment, the viscosity of the positive electrode slurry is 4000 mPa·s-30000 mPa·s. When the viscosity of the positive electrode slurry is within the above range, the slurry is not easy to precipitate and has good dispersibility, and at the same time, the slurry has good leveling property, which is helpful for coating.

[0032] In an embodiment, the solid content of the positive electrode slurry is 55%-65%. The above solid content is beneficial to improve the stability of the positive electrode slurry, and can also reduce the coating thickness and lower the battery internal resistance.

[0033] To solve the above technical problems, another technical solution adopted by the present application is to provide a dispersant comprising a polyester compound, the polyester compound comprising structural unit A and / or structural unit B, the chemical formula of the structural unit A is The chemical formula of the structural unit B is

[0034] Wherein, R1, R2 are selected from at least one of C0, C1-C18 alkyl, C6-C18 aryl; R3, R4 are selected from at least one of H, C1-C18 alkyl, C6-C18 aryl, ester group.

[0035] In this embodiment, the dispersant can improve the dispersibility of the positive electrode slurry, improve the uniformity and flexibility of the positive electrode sheet, so that the battery has higher capacity and stability.

[0036] In an embodiment, the polyester compound comprises structural unit C and / or structural unit D, the chemical formula of the structural unit C is The chemical formula of the structural unit D is Wherein, R5 is selected from any one of C1-C18 alkyl and C6-C18 aryl. In this embodiment, the provided polyester compound can be polycondensation of a polybasic acid and a dibasic alcohol, or polycondensation of a polyhydric alcohol and a dibasic acid. The carbon chain between the two ester groups in the polyester compound molecule can rotate freely, providing a certain flexibility. Through the regulation of the carbon chain, the flexibility effect can be enhanced.

[0037] In an embodiment, the polyester compound further comprises at least one substituent group G, G comprises any one of carboxylic acid group and its derivative, sulfonic acid group and its derivative, phosphonic acid group and its derivative. The substituent group G can ionize a negative ion, and then produce adsorption effect on the surface of the active material through the action of positive and negative charges, so as to produce electrostatic repulsion between the material particles, so as to achieve the dispersion purpose; or the substituent group G is a polar group, which can produce strong interaction force with the material surface, so as to keep a certain distance between the material particles, thereby further improving the dispersion effect of the dispersant.

[0038] To solve the above technical problems, another technical solution adopted by the present application is to provide a preparation method of a dispersant, comprising the following steps: providing a polybasic acid monomer or a polyhydric alcohol monomer, the polybasic acid monomer comprising The polyhydric alcohol monomer comprises Wherein, R1, R2 are respectively selected from at least one of C0, C1-C18 alkyl, C6-C18 aryl; R3, R4 are respectively selected from at least one of H, C1-C18 alkyl, C6-C18 aryl, ester group; the polybasic acid monomer is subjected to polycondensation reaction with the dibasic alcohol monomer to obtain the polyester compound of any one of the above embodiments; or the polybasic alcohol monomer is subjected to polycondensation reaction with the dibasic acid monomer to obtain the polyester compound of any one of the above embodiments. The dispersant prepared by the above method can improve the dispersibility of the slurry, and when applied to the electrode sheet, the flexibility of the positive electrode sheet can be improved.

[0039] In an embodiment, after the polycondensation reaction, the polyester compound is reacted with a halogen-substituted compound containing a substituent group G to obtain a polyester compound containing the substituent group G; the substituent group G includes any one of a carboxylic acid group and its derivative, a sulfonic acid group and its derivative, and a phosphonic acid group and its derivative. The substituent group G can ionize a negative ion, and then produce adsorption on the surface of the active material through the action of positive and negative charges, so as to produce electrostatic repulsion between the material particles, so as to achieve the dispersion purpose; or the substituent group G is a polar group, which can produce a strong interaction force with the material surface, so as to keep a certain distance between the material particles, thereby further improving the dispersion effect of the dispersant.

[0040] In an embodiment, the molar ratio of the substituent group G to the polybasic acid monomer is 1:(1-100); and the molar ratio of the substituent group G to the polybasic alcohol monomer is 1:(1-100). Through the above setting, the dispersant prepared has better dispersion and flexibility improvement effect.

[0041] To solve the above technical problems, another technical solution adopted by the present application is to provide a kind of electric equipment, it includes the above battery.Electric equipment at least has the same advantage as battery, can improve the storage of electric equipment.

[0042] The above description is only a summary of the technical solutions of the present application, in order to more clearly understand the technical means of the present application, which can be implemented according to the content of the specification, and in order to make the above and other purposes, characteristics and advantages of the present application more obvious and easy to understand, the following will describe the specific embodiments of the present application. BRIEF DESCRIPTION OF DRAWINGS

[0043] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings needed in the embodiment description will be briefly introduced as follows. Obviously, the drawings in the following description are only some embodiments of the present application, and those skilled in the art can also obtain other drawings according to these drawings without creating any creative labor.

[0044] Figure 1 It is a exploded structural schematic diagram of the battery according to one or more embodiments of the present application.

[0045] Figure 2 a decomposition structure diagram of a battery cell according to one or more embodiments of the present application;

[0046] Figure 3 a structure diagram of a vehicle according to one or more embodiments of the present application.

[0047] In the drawings:

[0048] 1000, vehicle; 300, motor; 200, controller; 100, battery; 10, case; 11, first portion; 12, second portion; 20, battery cell; 21, end cap; 21a, electrode terminal; 22, housing; 23, electrode assembly. DETAILED DESCRIPTION

[0049] In order to make the objectives, technical solutions and effects of the present application clearer and more explicit, the embodiments of the technical solutions of the present application will be described in detail below in conjunction with the drawings. The following embodiments are only used to more clearly illustrate the technical solutions of the present application, and therefore only serve as examples, and cannot be used to limit the protection scope of the present application.

[0050] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the present application belongs; the terms used herein are only for the purpose of describing specific embodiments, and are not intended to limit the present application; the terms "include" and "have" and any variations thereof in the specification and claims of the present application and the above description of drawings are intended to cover not exclusive inclusion.

[0051] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the term "a plurality of" refers to two or more (including two), and similarly, "a plurality of groups" refers to two or more groups (including two groups), and "a plurality of pieces" refers to two or more pieces (including two pieces), unless otherwise explicitly specified.

[0052] Reference herein to "an embodiment" means that a particular feature, structure, or characteristic described in connection with the embodiment can be included in at least one embodiment of the present application. The appearance of the phrase in various places in the specification does not necessarily all refer to the same embodiment, nor is it necessarily independent or alternative embodiments to other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0053] In the description of the embodiments of the present application, the term "and / or" is merely an association relationship of the associated objects, which means that there can be three relationships, for example, A and / or B, which can represent the three cases of A alone, A and B together, and B alone. In addition, the character " / " in this paper generally represents that the front and rear associated objects are a "or" relationship.

[0054] In this paper, the amount, ratio and other numerical values are presented in the form of range. It should be understood that such range format is for convenience and brevity, and should be flexibly understood, not only including the numerical values explicitly specified as range limits, but also including all individual numerical values or subranges covered in the range, as if each numerical value and sub-range is explicitly specified.

[0055] If there is no special description, all the steps of the present application can be carried out in sequence, randomly or in parallel, preferably in sequence. For example, the method comprises steps (a) and (b), which means that the method can comprise steps (a) and (b) in sequence, or steps (b) and (a) in sequence, or steps (a) and (b) in parallel. For example, the method can also comprise step (c), which means that step (c) can be added to the method in any order, for example, the method can comprise steps (a), (b) and (c), or steps (a), (c) and (b), or steps (c), (a) and (b), etc.

[0056] Lithium ion battery as a new green secondary battery, is widely used in electric vehicles, energy storage systems and renewable energy field. With the new development of lithium ion battery in China, lithium ion battery will realize the improvement in many aspects.

[0057] Please refer to Figure 1 , Figure 1FIG. 1 is a schematic diagram of a battery according to one or more embodiments. The battery 100 includes a case 10 and a battery cell 20 accommodated in the case 10. The case 10 is configured to accommodate the battery cell 20. The case 10 can have various configurations. In some embodiments, the case 10 can include a first portion 11 and a second portion 12. The first portion 11 and the second portion 12 are configured to cover each other and define an accommodation space for the battery cell 20. The second portion 12 can be a hollow structure with an open end, and the first portion 11 can be a plate-shaped structure configured to cover the open end of the second portion 12. Alternatively, the first portion 11 and the second portion 12 can each be a hollow structure with an open end, and the open end of the first portion 11 is configured to cover the open end of the second portion 12. The case 10 formed by the first portion 11 and the second portion 12 can have various shapes, such as a cylindrical shape, a cuboid shape, and the like.

[0058] In the battery 100, the battery cell 20 can be a plurality of battery cells 20. The plurality of battery cells 20 can be connected in series, in parallel, or in a mixed connection. The mixed connection means that the plurality of battery cells 20 are connected in series and in parallel. The plurality of battery cells 20 can be directly connected in series, in parallel, or in a mixed connection, and the plurality of battery cells 20 can be accommodated in the case 10. Alternatively, the plurality of battery cells 20 can be connected in series, in parallel, or in a mixed connection to form a battery module, and a plurality of battery modules can be connected in series, in parallel, or in a mixed connection to form a whole, which can be accommodated in the case 10. The battery 100 can further include other structures. For example, the battery 100 can further include a busbar configured to electrically connect the plurality of battery cells 20.

[0059] Each of the battery cells 20 can be a secondary battery or a primary battery. The battery cell 20 can be a lithium-sulfur battery, a sodium-ion battery, or a magnesium-ion battery, but is not limited thereto. The battery cell 20 can have a cylindrical shape, a flat shape, a cuboid shape, or other shapes.

[0060] Referring to FIG. 2, Figure 2 , Figure 2 FIG. 2 is a schematic diagram of a battery cell according to one or more embodiments. The battery cell 20 is the smallest unit constituting a battery. As shown in FIG. 2, Figure 2 , the battery cell 20 includes an end cap 21, a case 22, an electrode assembly 23, and other functional components.

[0061] The end cover 21 refers to a component that covers the opening of the shell 22 to isolate the internal environment of the battery cell 20 from the external environment. Without limitation, the shape of the end cover 21 can be adapted to the shape of the shell 22 to fit the shell 22. Optionally, the end cover 21 can be made of a material with certain hardness and strength, such as aluminum alloy, so that the end cover 21 is less likely to deform when subjected to extrusion collision, allowing the battery cell 20 to have higher structural strength and improved safety performance. The end cover 21 can be provided with functional components such as electrode terminals 21a. The electrode terminals 21a can be used to electrically connect with the electrode assembly 23 for outputting or inputting the electrical energy of the battery cell 20. In some embodiments, the end cover 21 can also be provided with a pressure relief mechanism for relieving the internal pressure of the battery cell 20 when the internal pressure or temperature reaches a threshold value. The material of the end cover 21 can also be various, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and the embodiments of the present application do not make special limitations thereon. In some embodiments, an insulating member can also be provided on the inner side of the end cover 21, which can be used to isolate the electrical connection components in the shell 22 from the end cover 21 to reduce the risk of short circuit. Exemplarily, the insulating member can be plastic, rubber, etc.

[0062] The shell 22 is a component for fitting the end cover 21 to form the internal environment of the battery cell 20, wherein the formed internal environment can be used to accommodate the electrode assembly 23, electrolyte and other components. The shell 22 and the end cover 21 can be independent components, and an opening can be provided on the shell 22, and the end cover 21 is covered on the opening to form the internal environment of the battery cell 20. Without limitation, the end cover 21 and the shell 22 can also be integrated, specifically, the end cover 21 and the shell 22 can form a common connecting surface before other components enter the shell, and when it is necessary to seal the internal environment of the shell 22, the end cover 21 is covered on the shell 22. The shell 22 can be various shapes and various sizes, such as cuboid, cylinder, hexagonal prism, etc. Specifically, the shape of the shell 22 can be determined according to the specific shape and size of the electrode assembly 23. The material of the shell 22 can be various, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and the embodiments of the present application do not make special limitations thereon.

[0063] The electrode assembly 23 is a component in which electrochemical reactions occur in the battery cell 20. One or more electrode assemblies 23 can be contained within the case 22. The electrode assembly 23 is mainly formed by winding or layering a positive electrode sheet and a negative electrode sheet, and a separator is generally provided between the positive electrode sheet and the negative electrode sheet. The positive electrode sheet and the negative electrode sheet have portions with active materials that constitute a main body of the electrode assembly, and portions without active materials that each constitute a tab. The positive electrode tab and the negative electrode tab can be located together at one end of the main body or at opposite ends of the main body. During charging and discharging of the battery, the positive electrode active material and the negative electrode active material react with the electrolyte, and the tab 23a connects the electrode terminal to form a current loop.

[0064] In some embodiments, the positive electrode tab includes a current collector and a positive electrode active layer disposed on the current collector.

[0065] The positive electrode active layer includes a positive electrode active material, which can include at least one of a lithium-containing phosphate of an olivine structure, a lithium transition metal oxide, and a modified compound of each thereof. However, the present application is not limited to these materials, and other conventional materials that can be used as a battery positive electrode active material can also be used. These positive electrode active materials can be used alone or in combination with two or more. Examples of the lithium transition metal oxide can include, but are not limited to, lithium cobalt oxide (e.g., LiCoO2), lithium nickel oxide (e.g., LiNiO2), lithium manganese oxide (e.g., LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (e.g., LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, which can also be referred to as NCM 333 ), LiNi 0.5 Co 0.2 Mn 0.3 O2, which can also be referred to as NCM 523 ), LiNi 0.5 Co 0.25 Mn 0.25 O2, which can also be referred to as NCM 211 ), LiNi 0.6 Co 0.2 Mn 0.2 O2, which can also be referred to as NCM 622 ), LiNi 0.8 Co 0.1 Mn 0.1 O2, which can also be referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (e.g., LiNi 0.85 Co 0.15 Al 0.05Li2FePO4, Li2MnPO4, Li2MnFePO4, Li2MnFePO4 / carbon composites, at least one of Li2FePO4, Li2MnPO4, Li2MnFePO4, Li2MnFePO4 / carbon composites, and modified compounds thereof. Examples of lithium-containing olivine-structured phosphates can include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (which can also be referred to simply as LFP)), a composite of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite of lithium manganese phosphate and carbon, lithium manganese iron phosphate, a composite of lithium manganese iron phosphate and carbon.

[0066] Preferably, the positive active material includes lithium manganese iron phosphate (LiFe x Mn 1-x PO4), lithium cobaltate (LiCoO2), lithium manganate (LiMn2O4), lithium iron phosphate (LiFePO4), high-nickel layered material Li 1+y (Ni a Co b Mn 1-a-b-c B c ) 1-y O2; wherein 0.05≤y≤0.05, 0.85≤a≤0.95, 0.01≤b≤0.10, 0≤c≤0.05, B is one or more of Zn 2+ , Mg 2+ , Al 3+ , Cr 3+ , Sc 3+ , Ga 3+ , La 3+ , Sm 3+ , Ti 4+ , Zr 4+ , Nb 5+ , W 6+ .

[0067] In an embodiment, the active layer of the positive material further includes a conductive agent and a binder; the conductive agent includes one or more of conductive carbon black, conductive graphite, carbon fiber, carbon nanotube, graphene, ketjen black, and acetylene black; the binder includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, acrylate, polyurethane.

[0068] The conductive agent imparts electrical conductivity to the electrode. The positive conductive material can include any electrically conductive material, so long as it does not cause chemical changes. Non-limiting examples of positive conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives), and mixtures thereof. Optionally, the conductive agent includes one or more of conductive carbon black, conductive graphite, carbon fiber, carbon nanotube, graphene, ketjen black, and acetylene black.

[0069] The binder improves the adhesion stability of the active layer and reduces the probability of powder falling. The binder can be one or more of styrene butadiene rubber (SBR), water-based acrylic resin, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyacrylic acid (PAA), carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA), and polyvinyl butyral (PVB). Alternatively, the binder includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, acrylate, and polyurethane.

[0070] In an embodiment, the active layer of the positive electrode material further includes the dispersant of any of the preceding embodiments or is prepared by the preparation method of any of the preceding embodiments. The dispersant is beneficial to improve the uniformity and flexibility of the positive electrode sheet.

[0071] In some embodiments, the negative electrode sheet includes a current collector and a negative active layer disposed on the current collector.

[0072] The negative active layer includes a negative active material, which includes but is not limited to carbon-based negative materials, silicon-based negative materials, tin-based negative materials, lithium titanate negative materials, metal lithium negative materials, etc.; specifically includes but is not limited to graphite materials, silicon-carbon materials, graphite-silicon monoxide materials, nano-silicon materials, silicon monoxide materials, and tin-based materials; more specifically includes one or more of natural graphite, artificial graphite, mesophase carbon microbeads (MCMB for short), hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel-structured Li4Ti5O12, and Li-Al alloy. 12

[0073] In some embodiments, the negative active layer can further include a binder, a conductive agent, and other optional additives. As an example, the conductive agent can be one or more of super conductive carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, Super P (SP), graphene, and carbon nanofibers. As an example, the binder can be one or more of styrene butadiene rubber (SBR), water-based acrylic resin, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyacrylic acid (PAA), carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA), and polyvinyl butyral (PVB). As an example, the other optional additives can be thickening and dispersing agents (such as sodium carboxymethyl cellulose CMC-Na) and PTC thermistor materials.

[0074] ​In some embodiments, the material of the isolation film can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The isolation film can be a single-layer film or a multi-layer composite film, and is not particularly limited. When the isolation film is a multi-layer composite film, the materials of the layers can be the same or different, and are not particularly limited.

[0075] In an embodiment, the electrolyte includes one or more of a carbonate solvent, an ether solvent.

[0076] The carbonate is usually a small molecule cyclic or chain carbonate; including but not limited to one or more of vinyl carbonate, propylene carbonate, butylene carbonate, vinylene carbonate, methyl propyl carbonate, dipropyl carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, fluorinated carbonate; and can also be at least one ester solvent of γ-butyrolactone, dimethyl sulfite, ethyl acetate, methyl acetate, methyl butyrate, ethyl butyrate, methyl propionate, ethyl propionate, propyl acetate, fluorinated carboxylic acid ester.

[0077] The ether solvent includes but is not limited to one or more of dimethyl ether, diethyl ether, tetrahydrofuran, methyl tetrahydrofuran, oxirane, 1,3-dioxolane, fluorinated ether, DME (ethylene glycol dimethyl ether), DEE (ethylene glycol diethyl ether), DEGDME (diethylene glycol dimethyl ether), TRGDME (triethylene glycol dimethyl ether), TEGDME (tetraethylene glycol dimethyl ether), dipropyl ether, and dibutyl ether.

[0078] In other embodiments, the electrolyte can also include a mixture of any one or several of an amine solvent, a sulfone solvent, and a nitrile solvent. The amine solvent includes at least one of N-methyl acetamide, N-methyl formamide, dimethyl formamide, diethyl formamide. The sulfone solvent includes at least one of dimethyl sulfoxide, cyclobutane sulfone, diphenyl sulfoxide, sulfurous acid chloride, dipropyl sulfone. The nitrile solvent includes at least one of acetonitrile, butanedinitrile, hexanedinitrile, pentanedinitrile. The electrolyte is preferably a high-voltage-resistant electrolyte, which has reduced acidity at high voltage, can facilitate the transport of active ions, significantly reduce the side reactions on the electrode surface, and improve the stability of the battery.

[0079] In some embodiments, the electrolyte further includes an electrolyte salt, which can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonylimide, lithium bis-trifluoromethanesulfonylimide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluoro oxalate borate, lithium difluoro oxalate borate, lithium difluoro di-oxalate phosphate, and lithium tetrafluoro oxalate phosphate.

[0080] In some embodiments, the electrolyte also optionally includes an additive. For example, the additive can include a negative electrode film-forming additive, a positive electrode film-forming additive, and can also include an additive capable of improving certain performance of the battery, such as an additive capable of improving overcharge performance of the battery, an additive capable of improving high-temperature or low-temperature performance of the battery, etc.

[0081] As previously described, the electrode assembly is a component in which electrochemical reactions occur in the battery cell. The electrode assembly is mainly formed by winding or layering a positive electrode sheet and a negative electrode sheet, and a separator is generally provided between the positive electrode sheet and the negative electrode sheet. Among them, the positive electrode sheet includes a current collector and a positive electrode active layer provided on the current collector. The positive electrode active layer includes a positive electrode active material, a conductive agent, and a binder, etc. In the preparation process of the positive electrode sheet, first, the positive electrode active material, the conductive agent, and the binder need to be fully stirred and mixed uniformly in a solvent to prepare a positive electrode slurry; then the positive electrode slurry is coated on the current collector and dried and cold-pressed to obtain the positive electrode sheet.

[0082] Therefore, the properties of the positive electrode slurry significantly affect the performance of the positive electrode sheet. In the positive electrode slurry, the solid content affects the stability of the slurry. Within a certain range, the higher the solid content of the slurry, the higher the stability of the slurry; and the slurry with high solid content can reduce the coating thickness and lower the internal resistance of the battery. However, the dispersion of the slurry with high solid content is insufficient, and gelation phenomenon is easy to occur, which can reduce the uniformity of the positive electrode sheet and cause loss of battery capacity.

[0083] In addition, increasing the coating thickness of the positive electrode slurry and the compaction density of the positive electrode sheet is beneficial to improving the energy density of the battery. However, in the case of large coating thickness and high compaction density, the flexibility of the positive electrode sheet is reduced, which can reduce the stability of the positive electrode sheet and cause the positive electrode sheet to break easily.

[0084] Accordingly, the present application provides a dispersant, the use of which can improve the dispersion of the positive electrode slurry, improve the uniformity and flexibility of the positive electrode sheet, and enable the battery to have higher capacity and stability. The dispersant can be applied to the positive electrode sheet of the battery, that is, the present application provides a battery, which includes a positive electrode sheet, the positive electrode sheet includes a current collector and a positive electrode material layer provided on at least one side of the current collector, the positive electrode material layer includes a positive electrode active material and a dispersant, the dispersant includes a polyester compound, the polyester compound includes structural unit A or structural unit B, the chemical formula of structural unit A is the chemical formula of structural unit B is wherein R1, R2 are each selected from at least one of C0, C1-C18 alkyl, C6-C18 aryl; R3, R4 are each selected from at least one of H, C1-C18 alkyl, C6-C18 aryl, ester group.

[0085] Wherein, C0 refers to a group containing 0 carbon atoms, i.e. the ester groups at both ends are directly connected to the middle carbon atom, C1-C18 alkyl refers to an alkyl chain containing 1 to 18 carbon atoms, and C6-C18 aryl refers to an aryl chain containing 6 to 18 carbon atoms.

[0086] In this embodiment, the provided dispersant selects a polyester as the main chain of the polymer. The ester group in the polyester is a strong polar group, which can produce a strong polarization effect. Multiple ester groups with similar distances can be combined together to produce a strong intermolecular force on the surface of the material particles, thereby adsorbing and causing the surface of the particles to form a double-layer structure to produce electrostatic repulsion. In addition, the oxygen atom on the ester group can also form a hydrogen bond with the group with weaker polarity on the surface of the particles. Further, the polyester branched chain can be introduced with a solvated segment to fully stretch in the solvent system, thereby playing a steric hindrance role to improve the dispersion capacity and subsequent stabilization effect, preventing the particles from re-aggregating after complete dispersion. Furthermore, the carbon chain between the two ester groups in the polyester compound can rotate freely, providing a certain flexibility to the dispersant. When applied to the electrode sheet, the polyester compound can be embedded into the chain of the rigid binder (such as PVDF), increasing the sliding ability of the PVDF chain and improving the flexibility of the electrode sheet. The positive electrode sheet of such a battery has good uniformity and flexibility, and the positive electrode sheet is not prone to breakage, so the capacity and stability of the battery are high. In addition, without damaging the structural stability of the positive electrode sheet, the coating thickness and the compaction density of the positive electrode sheet can be increased, thereby improving the energy density of the battery.

[0087] Wherein, the polyester is a polymer obtained by polycondensation of a polyhydric alcohol and a polybasic acid. In this embodiment, the provided polyester compound can be obtained by polycondensation of a polybasic acid and a dihydric alcohol, or by polycondensation of a polyhydric alcohol and a dibasic acid.

[0088] Specifically, a polybasic acid monomer and a dihydric alcohol can be selected to perform a polycondensation reaction to obtain a polyester compound. For example, a dibasic acid monomer can be selected to prepare a polyester compound, and a structural unit A is formed in the polyester compound. Alternatively, a polyhydric alcohol monomer and a dibasic acid can be selected to perform a polycondensation reaction to obtain a polyester compound. For example, a dihydric alcohol monomer can be selected to prepare a polyester compound, and a structural unit B is formed in the polyester compound. Alternatively, a polyester compound can only contain the structural unit A, or only contain the structural unit B, or simultaneously contain the structural units A and B in the same polyester compound.

[0089] In an embodiment, R1, R2are independently selected from at least one of C0, C1-C18 alkyl, C6-C18 aryl. R1, R2are located on the main chain of the polyester compound and are arranged between two ester groups. By selecting the above carbon chain structure, the carbon chain between the two ester groups in the polyester compound molecule can rotate freely, providing flexibility to the dispersant; by controlling the carbon chain, the flexibility effect can be enhanced.

[0090] In an embodiment, R3, R4are independently selected from at least one of H, C1-C18 alkyl, C6-C18 aryl, ester group. R3, R4are branched groups of the polyester compound, which can be introduced into the polyester compound as a solvating segment. The solvating segment has good compatibility with the dispersion medium (usually an organic solvent, such as N-methyl pyrrolidone), and can fully expand in the dispersion medium system, playing a steric hindrance effect to improve the dispersion capacity and subsequent stabilization effect, preventing the particles from re-aggregating after complete dispersion.

[0091] In an embodiment, the chemical formula of the ester group is wherein 0≤a≤6, R' is selected from any one of C1-C18 alkyl, C6-C18 aryl, polyoxyethylene ether segment, polyoxyethylene polyoxypropylene ether copolymer segment.

[0092] wherein C a refers to a carbon chain structure with a number of carbon atoms a, which can be an alkyl chain structure. The number of carbon atoms is 0-6. When the number of carbon atoms is 0, the ester group is directly connected to the main chain of the polyester compound.

[0093] In this embodiment, the introduction of carbon chain or polyether segment in R3and R4serves as a solvating segment that can fully expand in the solvent system, playing a steric hindrance effect to improve the dispersion capacity and subsequent stabilization effect, preventing the particles from re-aggregating after complete dispersion.

[0094] In an embodiment, the polyoxyethylene polyoxypropylene ether copolymer segment includes wherein 3≤b≤60; 0≤c≤60. The polyoxyethylene polyoxypropylene ether copolymer segment can serve as a solvating segment, and the degree of polymerization is within the above range, having a good solvating effect and improving the dispersion performance.

[0095] In an embodiment, the polyester compound includes structural unit C or structural unit D, the chemical formula of structural unit C is The chemical formula of structural unit D is wherein R5is selected from any one of C1-C18 alkyl, C6-C18 aryl.

[0096] As described above, the polybasic acid monomer can be used to react with the dibasic alcohol to obtain the polyester compound. The polybasic alcohol monomer can also be used to react with the dibasic acid to obtain the polyester compound. For example, the dibasic acid monomer can be used to prepare the polyester compound, and the dibasic alcohol used to react with the dibasic acid monomer can be For example, the dibasic alcohol monomer can be used to prepare the polyester compound, and the dibasic acid used to react with the dibasic alcohol monomer can be For example, the dibasic alcohol monomer can be used to prepare the polyester compound, and the dibasic acid used to react with the dibasic alcohol monomer can be The polyester compound can form the structural unit C: For example, the dibasic alcohol monomer can be used to prepare the polyester compound, and the dibasic acid used to react with the dibasic alcohol monomer can be For example, the dibasic alcohol monomer can be used to prepare the polyester compound, and the dibasic acid used to react with the dibasic alcohol monomer can be For example, the dibasic alcohol monomer can be used to prepare the polyester compound, and the dibasic acid used to react with the dibasic alcohol monomer can be The polyester compound can form the structural unit D:

[0097]

[0098] In this embodiment, R5 can rotate freely as the carbon chain between the two ester groups in the polyester compound molecule, providing flexibility to the dispersant; and by regulating the carbon chain, the flexibility effect can be enhanced.

[0099] In an embodiment, the polyester compound further comprises at least one substituent group G, and G comprises any one of a carboxylic acid group and a derivative thereof, a sulfonic acid group and a derivative thereof, and a phosphonic acid group and a derivative thereof.

[0100] The substituent group G can ionize a negative ion, and then produce an adsorption effect on the surface of the polar material through the positive and negative charge interaction, so as to produce electrostatic repulsion between the material particles, thereby achieving the dispersion purpose; or the substituent group G is a polar group, which can produce a strong interaction force with the material surface, so as to keep a certain distance between the material particles, thereby further improving the dispersion effect of the dispersant.

[0101] In some embodiments, the substituent group G is any one of a carboxylic acid group, a sulfonic acid group, and a phosphonic acid group. At this time, the substituent group G can ionize a negative ion, and different substituent groups G ionize different negative ions. By controlling the type of the substituent group G, different types of negative ions can be ionized, and the interaction forces produced by the different types of negative ions are also different, thereby realizing the adsorption effect on the surface of the material of different polarity through the positive and negative charge interaction, so as to produce electrostatic repulsion between the material particles, thereby achieving the dispersion purpose.

[0102] In some embodiments, the substituent group G is any one of a carboxylic acid group derivative, a sulfonic acid group derivative, and a phosphonic acid group derivative. The active hydrogen on the carboxylic acid group, the sulfonic acid group, and the phosphonic acid group is substituted by other substituents to obtain the derivative of the corresponding group. At this time, the substituent group G is a polar group, which can produce a strong interaction force with the material surface, so as to keep a certain distance between the material particles, thereby improving the dispersion effect of the dispersant.

[0103] In an embodiment, the substituent group G can further include a cationic group or an aromatic non-polar group. The cationic group can generate electrostatic interaction with the material containing negative charge, so that electrostatic repulsion is generated between the material particles, achieving the dispersion purpose. The aromatic non-polar group has excellent adsorption effect on the carbon-coated material, and can keep a certain distance between the material particles, thereby further improving the dispersion effect of the dispersant.

[0104] In an embodiment, the chemical formula of the carboxylic acid group and its derivative is and / or the chemical formula of the sulfonic acid group and its derivative is wherein d is greater than 1 and less than or equal to 12, and R6 is selected from any one of H, alkyl, alkyl alcohol, alkyl hydroxylamine, aliphatic ester group, and aromatic ester group; the chemical formula of the alkyl is the chemical formula of the alkyl alcohol is the chemical formula of the alkyl hydroxylamine is the chemical formula of the aliphatic ester group is the chemical formula of the aromatic ester group is e is 1-12, f is 1-16, and the number of carbon atoms in Ar is not more than 12.

[0105] In this embodiment, C d is a carbon chain with d carbon atoms, which can be an alkyl chain. It can play a solvation effect as a solvation segment; when R6 is H, the above group can ionize a negative ion, and then produce adsorption effect on the material surface through the action of positive and negative charges, so that electrostatic repulsion is generated between the material particles, achieving the dispersion purpose; when R6 is alkyl, alkyl alcohol, alkyl hydroxylamine, aliphatic ester group, and aromatic ester group, the polarity of the substituent group G can be improved, and a strong interaction force is generated with the material surface, so that a certain distance is kept between the material particles, thereby further improving the dispersion effect of the dispersant.

[0106] In an embodiment, the phosphonic acid group and its derivative include diester phosphonic acid and its derivative or monoester phosphonic acid and its derivative, the chemical formula of the diester phosphonic acid and its derivative is the chemical formula of the monoester phosphonic acid and its derivative is wherein R6 is selected from any one of H, alkyl, alkyl alcohol, alkyl hydroxylamine, aliphatic ester group, and aromatic ester group; the chemical formula of the alkyl is the chemical formula of the alkyl alcohol is the chemical formula of the alkyl hydroxylamine is the chemical formula of the aliphatic ester group is the chemical formula of the aromatic ester group is e is 1-12, f is 1-16, and the number of carbon atoms in Ar is not more than 12.

[0107] R6 is H, the above-mentioned group can ionize a negative ion, and then produce adsorption effect on the material surface through the positive and negative charge effect, so as to produce electrostatic repulsion between the material particles, so as to achieve the dispersion purpose; R6 is alkyl, alkyl alcohol, alkyl hydroxylamine, fatty ester group and aromatic ester group, which can improve the polarity of the substituted group G, and produce strong interaction force with the material surface, so as to keep a certain distance between the material particles, thereby further improving the dispersion effect of the dispersant.

[0108] In an embodiment, the two sides of the di-ester phosphonic acid and its derivatives are symmetrical polyester segments.

[0109] The substituted group G acts as an anchoring group and can be adsorbed on the surface of the material particles through ionic bonds, hydrogen bonds and van der Waals forces, so as to keep a certain distance between the material particles, thereby further improving the dispersion effect of the dispersant.

[0110] In an embodiment, G is an end group of the polyester compound. Through this arrangement, the dispersant can better interact with the material, thereby improving the dispersion effect.

[0111] In an embodiment, the substituted group G is a di-ester phosphonic acid and its derivatives, and the two ends of G are connected to symmetrical polyester segments.

[0112] In an embodiment, the polyester segments can be prepared first, and then the substituted group G is introduced at the end of the polyester segments.

[0113] In an embodiment, the dispersant comprises a structure as shown in formula (1) or a structure as shown in formula (2);

[0114]

[0115] In an embodiment, n is 3-100, A is an end-capping group, the end-capping group comprises one or more of an alkoxy group a benzyl alkoxy group an ester group an ester group an amide group one or more of a hydroxyl group -OH, an amino group -NH2 and a carboxyl group -COOH, g is 1-12, C h an alkyl segment or an aryl-containing segment, h is 1-18, and R is H, a C1-C12 alkyl group or a C6-C12 aryl group.

[0116] In an embodiment, the selection of the end-capping group depends on whether the last group is a hydroxyl group (alcohol end-capping) or a carboxyl group (acid end-capping), for example, when the last group is a hydroxyl group (alcohol end-capping), it can be The last group is a carboxyl group (acid-terminated) which can be The last group can also be

[0117] In this embodiment, the dispersant provided selects a polymer with polyester as the main chain, and the ester groups in the polyester are strong polar groups that can produce strong polarization effects. Multiple ester groups with similar distances can be combined together to produce strong intermolecular forces on the surface of the material particles and then be adsorbed, so that the particle surface forms a double-layer structure to produce electrostatic repulsion. At the same time, the oxygen atoms on the ester groups can also produce hydrogen bonding effects with the groups on the particle surface that have weaker polarity. Further, the polyester branched chains can be introduced with solvent segments to make them fully relaxed in the solvent system, to play a steric hindrance effect to improve the dispersion capacity and subsequent stabilization effect, to prevent the particles from re-aggregating after being fully dispersed. Furthermore, the carbon chains between the two ester groups in the polyester compound molecules can rotate freely, providing a certain flexibility. When applied to the electrode sheet, the polyester compound can be embedded in the rigid binder (such as PVDF) chains to increase the sliding ability of the PVDF chains and improve the flexibility of the electrode sheet.

[0118] In an embodiment, the weight percentage of the substituent group G segment in the polyester compound is less than 15%, the weight percentage of the solvent segments R1, R2, R3, R4, R5 is less than 65%, and the weight percentage of the polyester group is 3%-30%. By controlling the weight percentage of each group in the polyester compound within the above range, good adsorption effects between the dispersant and the material particles and between the dispersant and the dispersion medium can be produced, to achieve good dispersion effects, while the polymer molecular chain has good flexibility.

[0119] In an embodiment, the weight average molecular weight of the polyester compound is 500-100000. For example, it can be 500, 3000, 10000, 25000, 30000, 40000, 60000, 80000, 100000, etc., or a range composed of any two of the above values, such as 10000-30000, 25000-50000, 70000-85000, 90000-100000, etc. The dispersant has a large molecular weight, which can produce strong steric hindrance effects to fully disperse the material particles, while reducing their re-aggregation

[0120] In an embodiment, the polyester compound has a weight average molecular weight of 2000-50000. For example, it can be 2000, 3000, 8000, 10000, 25000, 30000, 40000, 50000, etc., or a range between any two of the above values, such as 2000-5000, 5000-15000, 15000-35000, 35000-50000, etc. The dispersant has a weight average molecular weight within the above range, which can further disperse the material particles by physical isolation and reduce the re-agglomeration of the dispersed particles.

[0121] The dispersant with the above structure can achieve good dispersion of the positive electrode material, and when applied to the positive electrode sheet, can improve the stability and flexibility of the positive electrode sheet, thereby reducing the capacity loss of the battery.

[0122] In an embodiment, the positive electrode active material includes one or more of lithium iron phosphate and lithium manganese iron phosphate. The positive electrode active material and the dispersant in the positive electrode material layer can interact with each other, so that the positive electrode active material particles maintain a certain distance from each other, and the dispersion effect is good.

[0123] In an embodiment, the membrane sheet resistance of the positive electrode sheet is 0.05Ω-0.30Ω. The membrane sheet resistance of the positive electrode sheet can be 0.05Ω, 0.10Ω, 0.135Ω, 0.15Ω, 0.20Ω, 0.25Ω, 0.30Ω, etc., or a range between any two of the above values, such as 0.05Ω-0.10Ω, 0.135Ω-0.20Ω, 0.20Ω-0.30Ω, etc. The membrane sheet resistance of the positive electrode sheet is small, which is conducive to reducing the internal resistance of the battery.

[0124] The application also provides a preparation method of the dispersant, including the following steps: providing a polybasic acid monomer or a polyhydric alcohol monomer, the polybasic acid monomer including The polyhydric alcohol monomer includes wherein R1 and R2 are each selected from at least one of C0, C1-C18 alkyl, and C6-C18 aryl; R3 and R4 are each selected from at least one of H, C1-C18 alkyl, C6-C18 aryl, and ester group; and the polybasic acid monomer is subjected to polycondensation with a dibasic alcohol monomer to obtain the polyester compound of any one of the above embodiments, or the polyhydric alcohol monomer is subjected to polycondensation with a dibasic acid monomer to obtain the polyester compound of any one of the above embodiments. The dispersant prepared by the above method can improve the dispersibility of the slurry, and when applied to the electrode sheet, can improve the flexibility of the positive electrode sheet.

[0125] In an embodiment, the condensation reaction is followed by: reacting the polyester compound with a halogen-substituted compound containing a substituent group G to obtain a polyester compound containing the substituent group G; the substituent group G includes any one of a carboxylic acid group and derivatives thereof, a sulfonic acid group and derivatives thereof, and a phosphonic acid group and derivatives thereof. The substituent group G can ionize a negative ion, and then produce adsorption on the surface of the polar material through the positive and negative charge effect, so as to produce electrostatic repulsion between the material particles, so as to achieve the dispersion purpose; or the substituent group G is a polar group, which can produce a strong interaction force with the material surface, so as to keep a certain distance between the material particles, thereby further improving the dispersion effect of the dispersant.

[0126] In an embodiment, the molar ratio of the substituent group G to the polybasic acid monomer is 1:(1-100); and the molar ratio of the substituent group G to the polyhydric alcohol monomer is 1:(1-100). By controlling the weight percentage of each group in the polyester compound within the above range, good adsorption between the dispersant and the material particles and between the dispersant and the dispersion medium can be produced, so as to achieve a good dispersion effect, and at the same time, the polymer molecular chain has good flexibility.

[0127] In an application scenario, the dispersant provided in the present application can be used as an additive in an electrode material slurry. For example, it can be applied to the positive electrode slurry of a lithium ion battery.

[0128] Taking the active material as lithium iron phosphate (LFP) as an example, the dispersion of the slurry with high solid content in the positive electrode slurry of the existing lithium ion battery is insufficient, and it is easy to gel. With the continuous development of the production process of lithium iron phosphate (LFP) and the requirement of increasing energy density, the particle size of LFP is continuously reduced, the specific surface area is continuously increased, and the surface energy is increased, so that the particles are not easy to disperse. Furthermore, under the condition of thick coating and high compaction density, the flexibility of the electrode sheet is poor, which leads to the problem of cracks in the electrode sheet.

[0129] Based on this, the dispersant provided in the present application is applied to the lithium iron phosphate (LFP) positive electrode slurry of a lithium ion battery. The ester group in the polyester mainly produces a strong adsorption effect on the particles in the system through hydrogen bonding, coordination or strong intermolecular forces, and at the same time, the long chain on the branched chain acts as a solvated chain segment to stabilize the dispersed particles through steric hindrance. Further, the polar anchoring group G is introduced into the branched polyester dispersant structure, so that the adsorption effect is more significant, and the dispersion performance is better improved.

[0130] In this embodiment, the dispersion mechanism of the dispersant is that a branched polymer capable of multi-site adsorption is designed for the polar surface of the LFP powder, G is a polar anchoring group acting on the polar LFP particle surface, and the main chain is mainly polyester, and the ester group in the polyester is a strong polar group, which can produce strong polarization effect, and multiple ester groups with similar distances can be combined together to produce strong intermolecular forces on the particle surface to adsorb the particle surface, so that a double-layer structure is formed on the particle surface to produce electrostatic repulsion, and the oxygen atom on the ester group can also form a hydrogen bond with the residues on the carbon coating on the LFP particle surface which has a weak polarity; meanwhile, the carbon chain or polyether chain segment introduced on the polyester branch chain is completely stretched as a solvation segment in the NMP system, which plays a steric hindrance effect to improve the dispersion capacity and subsequent stabilization effect, preventing the particles from re-aggregating after complete dispersion.

[0131] The dispersant increases the flexibility mechanism: the carbon chain between the two ester groups can rotate freely to provide a certain flexibility, and the carbon chain or polyether chain segment on the branch chain is also a good flexible group, which can be embedded into the PVDF chain to increase the sliding ability of the PVDF chain and improve the flexibility of the pole piece.

[0132] Based on this, the polyester compound dispersant provided in the application introduces anchoring groups and polar groups in the molecule to enhance the adsorption between the polymer and the surface of different polar particles and improve the dispersion performance. Meanwhile, the solvation segment with a certain steric hindrance is introduced to play a steric hindrance effect, prevent the powder from re-aggregating after dispersion, solve the problem of insufficient dispersion of the slurry under high solid content, and easily gel.

[0133] Furthermore, by introducing a flexible chain segment into the polymer molecule, the polymer tends to be linear, reducing the intermolecular sliding resistance and improving flexibility. It improves the problem of poor flexibility of the pole piece leading to pole piece cracks under thick coating and high pressure.

[0134] In other embodiments, the dispersant provided in the application can also be applied to the slurry of other positive active materials. For example, the substituent group G can form a hydrogen bond with the phosphate group on the surface of lithium iron phosphate, lithium manganese iron phosphate and other positive active materials, and form a hydrogen bond with the hydroxyl group on the surface of ternary positive active materials; it can also form a hydrogen bond with the hydroxyl group, carboxyl group and other functional groups on the surface of carbon nanotubes, graphene and other conductive agents. That is, different molecular structures of dispersants can be selected according to the type of positive active material.

[0135] The application also provides a positive electrode slurry, which comprises a positive active material, a dispersant and a solvent, and the dispersant is the dispersant of any one of the above embodiments or prepared by the preparation method of the dispersant of any one of the above embodiments. The dispersion of the positive electrode slurry is good, which is beneficial to improve the uniformity and flexibility of the positive electrode pole piece.

[0136] In an embodiment, the dispersant accounts for 0.01%-3.0% of the total weight of the positive electrode slurry. For example, it can be 0.01%, 0.05%, 0.1%, 0.16%, 0.2%, 0.5%, 0.8%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, etc., or a range between any two of the above values, such as 0.01%-0.05%, 0.1%-0.16%, 0.1%-0.2%, 0.8%-1.0%, 2.5%-3.0%, etc.

[0137] When the dispersant accounts for 0.01%-3.0% of the total weight of the positive electrode slurry, the positive electrode slurry can achieve good dispersion effect, and the flexibility of the positive electrode sheet can be improved. At the same time, the influence of the dispersant on the proportion of the positive electrode active material can be reduced, which is conducive to improving the mass proportion of the positive electrode active material and the energy density and specific capacity of the battery.

[0138] In an embodiment, the dispersant accounts for 0.03%-2.0% of the total weight of the positive electrode slurry. For example, it can be 0.03%, 0.05%, 0.1%, 0.16%, 0.2%, 0.25%, 0.5%, 0.8%, 1.0%, 1.5%, 2.0%, etc., or a range between any two of the above values, such as 0.03%-0.05%, 0.1%-0.16%, 0.2%-0.25%, 0.8%-1.0%, 1.5%-2.0%, etc.

[0139] When the dispersant accounts for 0.03%-2.0% of the total weight of the positive electrode slurry, the positive electrode slurry can achieve good dispersion effect, and the influence of the dispersant on the proportion of the positive electrode active material can be reduced, which is conducive to improving the mass proportion of the positive electrode active material and the energy density and specific capacity of the battery.

[0140] In an embodiment, the viscosity of the positive electrode slurry is 4000 mPa·s-30000 mPa·s. For example, it can be 4000 mPa·s, 4500 mPa·s, 5000 mPa·s, 6000 mPa·s, 8000 mPa·s, 10000 mPa·s, 12500 mPa·s, 15000 mPa·s, 20000 mPa·s, 22000 mPa·s, 26000 mPa·s, 29500 mPa·s, 30000 mPa·s, etc., or a range between any two of the above values, such as 4000 mPa·s-4500 mPa·s, 6000 mPa·s-8000 mPa·s, 12500 mPa·s-15000 mPa·s, 22000 mPa·s-26000 mPa·s, 29500 mPa·s-30000 mPa·s, etc.

[0141] The viscosity of the positive electrode slurry is in the above range, the slurry is not easy to precipitate and has good dispersibility, and meanwhile the slurry has good leveling property, which is helpful for coating.

[0142] In an embodiment, the solid content of the positive electrode slurry is 55%-65%. For example, it can be 55%, 55.6%, 56.4%, 58%, 60%, 62.3%, 62.5%, 63%, 65%, etc., or a range formed by any two of the above values, such as 55%-55.6%, 56.4%-60%, 62.3%-65%, etc. The above solid content is helpful for improving the stability of the positive electrode slurry, and can also reduce the coating thickness and lower the battery internal resistance.

[0143] In some embodiments, the positive electrode slurry is prepared as follows: the functional components such as the positive electrode active material, the conductive agent, the binder, the dispersant, and the solvent are added into a stirring tank in a certain proportion and feeding sequence, and are uniformly dispersed and mixed to obtain a slurry suspension system.

[0144] The prepared positive electrode slurry is not stratified, and has no obvious standing viscosity rebound, slow stirring without sedimentation, and gelation phenomenon.

[0145] The application also provides a positive electrode tab, which comprises a current collector and a positive electrode material layer arranged on the current collector, wherein the positive electrode material layer comprises a positive electrode active material and a dispersant, and the dispersant is the dispersant of any one of the above embodiments or is prepared by the preparation method of the dispersant of any one of the above embodiments. The positive electrode tab has good uniformity and flexibility; the coating thickness and the compaction density of the positive electrode tab can be improved without damaging the structural stability of the positive electrode tab, so that the energy density of the battery is improved.

[0146] In some embodiments, the positive electrode slurry of any one of the above embodiments is coated on a positive electrode current collector, and a positive electrode film is obtained after drying in an oven. Then, the positive electrode film is cold-pressed according to the design compaction thickness to obtain a positive electrode tab.

[0147] In some embodiments, the use of the electrochemical device of the present application is not particularly limited and can be used in any electronic device known in the art. The battery disclosed in the embodiments of the present application can be used in an electric device using a battery as a power source or a variety of energy storage systems using a battery as an energy storage element. That is, an electric device is provided, and in some embodiments, the electric device of the present application can be used, but is not limited to, a notebook computer, a pen input computer, a mobile computer, an electronic book player, a portable telephone, a portable facsimile, a portable copier, a portable printer, a head-mounted stereo headphone, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini disc, a transceiver, an electronic organizer, a calculator, a memory card, a portable recorder, a radio, a backup power supply, an electric motor, an automobile, a motorcycle, a power-assisted bicycle, a bicycle, a ship, a spacecraft, a lighting appliance, a toy, a game machine, a clock, an electric tool, a flash, a camera, a household large storage battery, and a lithium ion capacitor, etc.

[0148] The electric device can select a battery cell, a battery module, or a battery pack according to its use requirements.

[0149] Please refer to Figure 3 , Figure 3 is a structural schematic diagram of a vehicle according to one or more embodiments. The vehicle 1000 can be a fuel automobile, a gas automobile, or a new energy automobile, and the new energy automobile can be a pure electric automobile, a hybrid automobile, or a range extended automobile, etc. The vehicle 1000 is internally provided with a battery 100, which can be arranged at the bottom, the head, or the tail of the vehicle 1000. The battery 100 can be used for power supply of the vehicle 1000, for example, the battery 100 can be used as an operating power source of the vehicle 1000. The vehicle 1000 can further include a controller 200 and a motor 300, and the controller 200 is used to control the battery 100 to supply power to the motor 300, for example, to meet the working power demand of the vehicle 1000 during starting, navigation, and driving.

[0150] In some embodiments of the present application, the battery 100 can not only be used as an operating power source of the vehicle 1000, but also be used as a driving power source of the vehicle 1000, to replace or partially replace fuel or natural gas to provide driving power for the vehicle 1000.

[0151] In order to make the technical problems, technical solutions, and beneficial effects solved by the embodiments of the present application clearer, further detailed description will be made in combination with the embodiments and the drawings. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative, but not as any limitation on the present application and its application. Based on the embodiments in the present application, all other embodiments obtained by a person of ordinary skill in the art without creative labor fall within the scope of protection of the present application.

[0152] Example 1:

[0153] (I) Preparation of dispersant

[0154] (1) Perform polycondensation with a ternary acid and a binary alcohol as monomers. Among them, a small amount of alcohol is added to perform an esterification reaction with the ternary acid first to obtain a branched binary acid containing an ester group.

[0155]

[0156] (2) Then, the binary acid and the binary alcohol perform polycondensation reaction under the catalysis of concentrated sulfuric acid to obtain a branched polyester product; wherein the degree of polymerization can be controlled by controlling the reaction conditions and the feeding ratio, and the degree of polymerization can be increased by appropriately prolonging the reaction time and increasing the reaction temperature; then the terminal hydroxyl group of the polyester reacts with a halide under the catalysis of a base to realize end-capping, and then two molecules of the end-capped polyester perform phosphonate esterification reaction with phosphorus oxychloride to obtain a phosphonate ester product with a symmetrical structure, and finally hydrolysis reaction occurs with a small amount of water in the system to obtain the dispersant 1.

[0157]

[0158] (II) Preparation of lithium ion battery

[0159] 1. The positive active material lithium iron phosphate, the conductive agent acetylene black, the binder PVDF, and the dispersant 1 are weighed according to the weight ratio of 97.5:1.5:0.5:0.5, are fully stirred and mixed uniformly in an N-methylpyrrolidone solvent system, are coated on an Al foil by extrusion coating or transfer coating, are dried, are cold-pressed, and a positive electrode sheet is obtained.

[0160] 2. The negative active material artificial graphite, the conductive agent acetylene black, the binder carboxymethyl cellulose, and the dispersant butadiene styrene rubber are weighed according to the weight ratio of 96:2:1:1, are fully stirred and mixed uniformly in a deionized water solvent system, are coated on a Cu foil, are dried, are cold-pressed, and a negative electrode sheet is obtained.

[0161] 3. A PE porous polymer film is used as a separator. The positive electrode sheet, the separator, and the negative electrode sheet are wound in order and to size, an electric core is prepared after packaging, liquid injection, formation, and exhaust processes, and a lithium ion battery is obtained.

[0162] Example 2:

[0163] The polyester is prepared in the same manner as in Example 1, except that the phosphonate esterification controls the ratio of phosphorus oxychloride to polyester chain segment to be 1:1.05.

[0164] Example 3:

[0165] The previous steps are the same as in Example 1, the anchoring group step is also carried out under base catalysis, and is reacted with C1C4H9COOH to introduce the anchoring group, and the subsequent steps are also the same as in Example 1.

[0166]

[0167] Example 4:

[0168] The previous steps are the same as in Example 1, the anchoring group step is also carried out under base catalysis, and is reacted with C1C4H9SO3H to introduce the anchoring group, and the subsequent steps are also the same as in Example 1

[0169]

[0170] Examples 5-8:

[0171] The difference from Example 1 is that the solvated segment groups R1, R2, R3, R4, R5 of the dispersant are changed.

[0172] Examples 9-10:

[0173] The difference from Example 1 is that the polymerization degree of the polyester compound is adjusted.

[0174] Example 11:

[0175] The difference from Example 1 is that the main chain structure of the polyester compound is adjusted.

[0176] Example 12:

[0177] The difference from Example 1 is that the amount of the dispersant added is adjusted.

[0178] Comparative Example:

[0179] 1. The positive active material lithium iron phosphate, the conductive agent acetylene black, the binder PVDF, and the dispersant butadiene rubber are weighed according to the weight ratio of 97.5:1.5:0.5:0.5, and are fully stirred and mixed uniformly in an N-methylpyrrolidone solvent system, and are coated on an Al foil using extrusion coating or transfer coating, and are dried and cold-pressed to obtain a positive electrode sheet.

[0180] 2. The negative active material artificial graphite, the conductive agent acetylene black, the binder carboxymethyl cellulose, and the dispersant butadiene rubber are weighed according to the weight ratio of 96:2:1:1, and are fully stirred and mixed uniformly in a deionized water solvent system, and are coated on a Cu foil, dried, and cold-pressed to obtain a negative electrode sheet.

[0181] 3. A PE porous polymer film is used as a separator. The positive electrode sheet, the separator, and the negative electrode sheet are sequentially and dimensionally wound to form a battery cell, which is then packaged, injected, formed, and vented to obtain a lithium ion battery.

[0182] Performance test

[0183] 1. Material characterization

[0184] (1) Dispersant infrared characterization

[0185] The battery is disassembled, the positive electrode sheet is disassembled, an organic solvent is selected to treat the material layer of the positive electrode sheet, the inorganic material is removed, the organic matter is dissolved and separated, the polyester compound is obtained by using chromatographic separation technology for separation and purification, and qualitative test is performed. By using a Bruker Tensor37 infrared spectrometer, by using a spectrum pure potassium bromide tablet as a carrier, the sample solution to be tested is dropped on the potassium bromide tablet or mixed together during grinding to press a tablet. The infrared scanning interval is 4000cm -1 to 400cm -1 , the scanning resolution is 16cm -1 , and the repeated scanning is 16 times.

[0186] (2) Dispersant weight average molecular weight test

[0187] A Waters 2695Isocratic HPLC gel chromatograph (differential refractive detector 2141) is used. A polystyrene solution sample with a mass fraction of 3.0% is used as a reference, and a matching chromatographic column (oil: Styrage l HT5DMF7.8*300mm+Styrage l HT4) is selected. A 3.0% polymer solution is prepared by using purified N-methyl pyrrolidone (NMP) solvent, and the prepared solution is placed for one day for standby. During testing, a syringe is used to suck tetrahydrofuran for flushing several times. Then 5ml of experimental solution is sucked, the air in the syringe is excluded, and the needle tip is dried. Finally, the sample solution is slowly injected into the sample port. After the indicator is stable, the data is obtained.

[0188] (3) Polymerization degree test

[0189] After obtaining the weight average molecular weight data of the dispersant, the polymerization degree of the dispersant is obtained in combination with the mass of the monomer.

[0190] 2. Positive electrode slurry performance test

[0191] (1) Slurry solid content

[0192] Take the copper foil in the weight loss rate measuring instrument and weigh it, record it as M0, and clear it;

[0193] Take the positive electrode slurry, a small amount of which is coated on the copper foil, and then put it into the water content measuring instrument and weigh it, record it as M1; close the equipment and start drying; after the end, record the weighing data, record it as M2, and calculate the solid content, the solid content is (M2-M0) / (M1-M0).

[0194] (2) Slurry stability test

[0195] After the slurry is stirred for 30 min, a certain amount of the slurry is poured into the sample bottle of the stability tester. After the sample bottle is placed, the test tower cover is closed, the test tower cover is opened, the scanning curve of the test interface begins to appear, the sample stability test begins, and the test is continuously performed for 72 h or more to complete the test.

[0196] (3) Slurry viscosity

[0197] A rotary viscometer model DV-2TLV Brookfield viscometer is used. During use, an appropriate rotor is selected according to the viscosity of the slurry. The parameter is adjusted to 12 r / min. After the measurement starts, pay attention to the screen display. When the number no longer jumps obviously, and the right measurement progress rises from the bottom to the top, record the data.

[0198] 3. Battery performance test

[0199] (1) Positive electrode sheet brittleness test

[0200] Take a defect-free positive electrode sheet and cut it into a sample with a length of 20 cm and a width of 2.5 cm along the longitudinal direction. The number of samples is ≥8. First, pre-fold the sample, then place the film on the test platform, and roll it once with a 2 kg cylindrical roller. If it is transparent, the brittleness transparency frequency is 1. If it is not transparent, repeat the reverse folding and rolling. Observe the fold mark against the light to observe whether it is transparent or broken. Record the actual folding number and take the average as the test result.

[0201] (2) Film resistance

[0202] Cut the dried positive electrode slurry (film layer) into small round pieces with a diameter of 3 mm at the left, middle, and right of the positive electrode sheet. Turn on the power of the Yuntian Technology electrode resistance meter, place it in the appropriate position of the electrode resistance meter "probe", click the "start" button, and read the data when the display is stable. Test two positions for each small round piece. Finally, calculate the average of six measurements to get the resistance of the electrode film layer.

[0203] (3) First coulomb efficiency

[0204] At 25°C, charge the battery of the above examples and comparative examples at a rate of 0.1C to a voltage of 4.3V. The charge capacity at this time is recorded as the first cycle charge capacity of the secondary battery. Then, after standing for 5 min, discharge the battery at a rate of 0.1C to a voltage of 2.0V. Stand for 5 min. This is one charge-discharge cycle. The discharge capacity of this cycle is recorded as the first cycle discharge capacity of the secondary battery, which is the initial capacity of the secondary battery.

[0205] The first cycle coulomb efficiency of the secondary battery (%) = first cycle discharge capacity / first cycle charge capacity x 100%.

[0206] (4) Capacity retention rate at 45℃

[0207] The battery in the examples and comparative examples was charged at 1 / 3C constant current to 3.65V, then charged at 3.65V constant voltage to a current of 0.05C, rested for 10 min, and then discharged at 1 / 3C to 2.5V at 45℃, and the capacity obtained was recorded as the initial capacity CO. The above steps were repeated on the same battery, and the discharge capacity of the battery after the nth cycle was recorded at the same time, and then the capacity retention rate of the battery after each cycle was: Pn = Cn / CO x 100%.

[0208] During the test, the first cycle corresponds to n = 1, the second cycle corresponds to n = 2, and the 100th cycle corresponds to n = 100. The battery capacity retention rate data corresponding to Example 1 in Table 1 is the data measured after 300 cycles under the above test conditions, i.e. the value of P300.

[0209] Table 1: Parameter table of dispersants of each example and comparative example

[0210]

[0211] Note: The feed ratio refers to the molar ratio of polybasic acid monomer, polyol monomer and halide; "EO" refers to a polyoxyethylene ether chain segment, "PO" refers to a polyoxypropylene ether chain segment, and the polyester type is the main chain structure of the polyester compound, formula 1 is Formula 2 is "Proportion" refers to the proportion of the dispersant in the total weight of the positive electrode slurry.

[0212] Table 2: Performance parameter table of each example and comparative example

[0213]

[0214] Note: "Sheet brittleness" refers to the number of times of folding the sheet and transmitting light; "capacity retention rate" refers to the capacity retention rate after 300 cycles at 45℃.

[0215] III. Analysis of positive electrode sheet and battery performance test results

[0216] From the above example data, it can be concluded that the dispersant provided by the application can achieve good dispersion of the positive electrode slurry, and when applied to the positive electrode sheet, the positive electrode sheet has good flexibility, which is beneficial to improve the stability of the battery; and reduces the resistance of the positive electrode sheet, which is beneficial to improve the initial efficiency and capacity retention rate of the battery.

[0217] In addition, by regulating the type of anchoring group, the type of solvated segment, the polymerization degree and the added amount of dispersant, the dispersing effect of the dispersant can be adjusted: Comparative Examples 1-4, different anchoring groups G have good effects, among which the phosphonic acid of double ester (Example 1) is better than the phosphonic acid of single ester (Example 2); Comparative Examples 1, 5-8, different solvated segments are screened, the one containing polyoxyethylene ether and polyoxypropylene ether segment (Example 1) is better than the pure polyoxyethylene ether and alkyl segment (Examples 5-7), and better than the alkyl segment and alkyl segment (Example 5); Comparative Examples 1, 9-10, different polymerization degrees of polyester compounds have good effects; Comparative Examples 1, 12, different added amounts of polyester compounds have good effects.

[0218] The above only describes the embodiments of the present application, and does not limit the patent scope of the present application, and any equivalent structure or equivalent process transformation using the content of the specification and drawings, or direct or indirect application in other related technical fields, are also included in the patent protection scope of the present application.

Claims

1. A battery, characterized by The battery includes a positive electrode sheet including a current collector and a positive electrode material layer provided on at least one side of the current collector, the positive electrode material layer including a positive electrode active material and a dispersing agent, the dispersing agent including a polyester compound, the polyester compound including structural unit A and / or structural unit B, the structural unit A having a chemical formula of the structural unit B having a chemical formula of wherein R1, R2 are independently selected from at least one of C0, C1-C18 alkyl, C6-C18 aryl, ester group; R3, R4 are independently selected from at least one of H, C1-C18 alkyl, C6-C18 aryl, ester group.

2. The battery of claim 1, wherein The chemical formula of the ester group is wherein 0≤a≤6, R' is selected from any one of C1-C18 alkyl, C6-C18 aryl, polyoxyethylene ether segment, polyoxyethylene polyoxypropylene ether copolymer segment.

3. The battery of claim 2, wherein the cathode is a lithium cobalt oxide cathode. The polyoxyethylene polyoxypropylene ether copolymer segment includes wherein 3≤b≤60; 0≤c≤60.

4. The battery of any one of claims 1-3, wherein the positive active material comprises one or more of lithium iron phosphate, lithium manganese iron phosphate.

5. The battery of any one of claims 1-4, wherein the positive active material comprises one or more of lithium iron phosphate, lithium manganese iron phosphate.

6. The battery of any one of claims 1-5, wherein the positive active material comprises one or more of lithium iron phosphate, lithium manganese iron phosphate. The coating amount of the positive electrode material layer is 300-450 g / 1540.25 mm 2 .

7. The battery of any one of claims 1-6, wherein the positive active material comprises one or more of lithium iron phosphate, lithium manganese iron phosphate. The compacted density of the positive electrode material layer is 2.4-2.8 g / cm 2 . The sheet resistance of the positive electrode sheet is 0.05 Ω-0.30 Ω. wherein R5 is selected from any one of C1-C18 alkyl, C6-C18 aryl, ester group.

8. The battery of any one of claims 1 to 7, wherein, The polyester compound includes structural unit C and / or structural unit D, the chemical formula of the structural unit C is The chemical formula of the structural unit D is The polyester compound further comprises at least one substituent group G, and the G comprises any one of a carboxylic acid group and a derivative thereof, a sulfonic acid group and a derivative thereof, a phosphonic acid group and a derivative thereof.

9. The battery of any one of claims 1 to 8, wherein, The G is an end group of the polyester compound.

10. The battery of claim 9, wherein the electrolyte is a mixture of LiPF6 and LiBF4.

11. The battery of claim 9 or 10, wherein the dispersant is selected from any one of the following structures: wherein d is greater than 1 and less than or equal to 12, and R6 is selected from any one of H, alkyl, alkyl alcohol, alkyl hydroxylamine, aliphatic ester group, aromatic ester group; The chemical formula of the carboxylic acid group and its derivatives is and / or The chemical formula of the sulfonic acid group and its derivatives is 12. The battery of claim 9 or 10, wherein the dispersant is selected from any one of the following structures: The alkyl group has the formula The alkyl alcohol has the formula The alkyl hydroxylamine has the formula The fatty ester group has the formula The aromatic ester group has the formula e has a value of 1-12, f has a value of 1-16, and the number of carbon atoms in Ar is no more than 12. wherein R6 is selected from any one of H, alkyl, alkyl alcohol, alkyl hydroxylamine, aliphatic ester group, aromatic ester group; The chemical formula of the phosphonic acid group and its derivatives is The dispersant comprises a structure as shown in formula (1) or a structure as shown in formula (2). The alkyl group has the formula The alkyl alcohol has the formula The alkyl hydroxylamine has the formula The fatty ester group has the formula The aromatic ester group has the formula e has a value of 1-12, f has a value of 1-16, and the number of carbon atoms in Ar is no more than 12.

13. The battery of any one of claims 1 to 12, wherein, 14. The battery of claim 13, wherein the dispersant is selected from any one of the following structures: wherein n has a value ranging from 3 to 100, A is a capping group, said capping group comprising an alkoxy group phenylalkoxy ester group ester group amide group one or several of hydroxyl group -OH, amino group -NH2 and carboxyl group -COOH, g has a value ranging from 1 to 12, C h is an alkyl segment or an aryl-containing segment, h has a value ranging from 1 to 18, R is H, C1-C12 alkyl or C6-C12 aryl. The weight percentage of the substituent group G segment in the polyester compound is less than 15%, the weight percentage of the solvated segment R1, R2, R3, R4, R5 is less than 65%, and the weight percentage of the polyester group is 3%-30%. The weight average molecular weight of the polyester compound is 500-100000.

15. The battery of any one of claims 1 to 14, wherein, The weight average molecular weight of the polyester compound is 2000-50000.

16. The battery of claim 15, wherein the cathode comprises a lithium metal oxide. wherein R1, R2 are independently selected from at least one of C0, C1-C18 alkyl, C6-C18 aryl; R3, R4 are independently selected from at least one of H, C1-C18 alkyl, C6-C18 aryl, ester group.

17. A positive electrode slurry, characterized by, A positive electrode active material, a dispersing agent, and a solvent, the dispersing agent including a polyester compound, the polyester compound including structural unit A and / or structural unit B, the structural unit A having a chemical formula of the structural unit B having a chemical formula of The dispersant accounts for 0.01%-3.0% of the total weight of the positive electrode slurry.

18. The positive electrode slurry of claim 17, wherein, The dispersant accounts for 0.03%-2.0% of the total weight of the positive electrode slurry.

19. The positive electrode slurry of claim 18, wherein, The viscosity of the positive electrode slurry is 4000 mPa·s-30000 mPa·s.

20. The positive electrode slurry according to any one of claims 17 to 19, wherein The solid content of the positive electrode slurry is 55%-65%.

21. The positive electrode slurry according to any one of claims 17 to 19, wherein the positive electrode slurry contains 0.1 to 10 mass% of the binder. wherein R1, R2 are independently selected from at least one of C0, C1-C18 alkyl, C6-C18 aryl; R3, R4 are independently selected from at least one of H, C1-C18 alkyl, C6-C18 aryl, ester group.

22. A dispersant characterized by, comprising a polyester compound comprising structural unit A and / or structural unit B, the chemical formula of the structural unit A is the chemical formula of the structural unit B is wherein R5 is selected from any one of C1-C18 alkyl, C6-C18 aryl.

23. The dispersant of claim 22, wherein The polyester compound includes structural unit C and / or structural unit D, the chemical formula of the structural unit C is The chemical formula of the structural unit D is ​ 24. The dispersant of claim 22 or 23, wherein The polyester compound further comprises at least one substituent group G, which comprises any one of a carboxylic acid group and derivatives thereof, a sulfonic acid group and derivatives thereof, a phosphonic acid group and derivatives thereof.

25. A method of preparing a dispersant, characterized by, comprising the steps of: A polyacid monomer or a polyol monomer is provided, the polyacid monomer comprising The polyol monomer comprises wherein R1, R2 are independently selected from at least one of C0, C1-C18 alkyl, C6-C18 aryl; R3, R4 are independently selected from at least one of H, C1-C18 alkyl, C6-C18 aryl, ester group. polycondensation of the polybasic acid monomer with a dibasic alcohol monomer to obtain the polyester compound of any one of claims 22-24; or polycondensation of the polyhydric alcohol monomer with a dibasic acid monomer to obtain the polyester compound of any one of claims 22-24.

26. The method for preparing the dispersant as described in claim 25, characterized in that, comprising the steps of: reacting the polyester compound with a halogen-substituted compound containing substituent group G to obtain a polyester compound containing substituent group G; The substituent group G comprises any one of a carboxylic acid group and derivatives thereof, a sulfonic acid group and derivatives thereof, a phosphonic acid group and derivatives thereof.

27. The method of claim 25 or 26, wherein, The molar ratio of substituent group G to polybasic acid monomer is 1: (1-100); and the molar ratio of substituent group G to polyhydric alcohol monomer is 1: (1-100).

28. An electrical device, comprising: The electric device comprises the battery of any one of claims 1-16.

Citation Information

Cited By

  • Battery, positive electrode sheet and slurry, dispersant, and preparation method

    EP4769571A1